ChemInform Abstract: Ruthenium‐Catalyzed α‐(Hetero)arylation of Saturated Cyclic Amines: Reaction Scope and Mechanism. Issue 51 (17th December 2013) - Peschiulli, Aldo; Smout, Veerle; Storr, Thomas E.; Mitchell, Emily A.; Elias, Zdenek; Herrebout, Wouter; Berthelot, Didier; Meerpoel, Lieven; Maes, Bert U. W.
Abstract The scope of the C2‐arylation and ‐heteroarylation of 1‐(pyridin‐2‐yl)piperidines and related 5‐, 6‐, and 7‐membered N‐heterocycles is described using boronic acid esters and a catalytic amounts of Ru3(CO)12.